British humanitarianism and the Russian famine, 1891–2. Issue 246 (17th October 2016) - Kelly, Luke
Abstract: In 1891, southern Russia experienced a famine which affected 30–40 million people in an area the size of France, killing 650, 000 in the highest estimates. The response of the Russian government was widely criticized by both opponents within Russia and observers abroad. This article analyses the response of the British liberal press and the Quaker relief fund, considering how the famine and its causes were presented with respect to the tsarist government's culpability and ideas of Russian backwardness. It goes on to show how the framing of Quaker relief work highlighted these ideas of Russian underdevelopment and mismanagement, and advanced a liberal internationalist position within Britain. It is argued that we cannot explain the appeal of humanitarianism purely by its aesthetics of suffering and sympathy, but must also look to a wider range of social and political values held by its protagonists.